Beckon the dragon: How businesses can attract the Chinese consumers through digital marketing - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
With a population of more than 1.3 billion people, China is one market that any business would be remiss not to attract. But, with the population spread over an area of 9,600,000 sq km, how do businesses ensure their messages get through to their potential customers?